Investigate the effect of ground tyre rubber as a reinforcement filler in natural rubber hybrid composites. Issue 2 (3rd April 2023) - Kaliyappan, P.; Dhananchezian, M.
ABSTRACT: This paper investigates the effect of various proportions of Ground Tyre Rubber (GTR) blends with Natural Rubber (NR)/Ethylene Propylene Diene Monomer (EPDM) or NR/Chloroprene Rubber (CR) composites. The NR (95 phr) composites were developed with 5 phr of EPDM or 5 phr of CR along with different ratios of GTR (0, 10, 20, 30, and 40 phr) by a two-roll mill and hydraulic press. The interfacial adhesion of NR/EPDM and NR/CR composites was improved with the addition of nylon 6 at 5 phr. Hence, the silica (20 phr) and carbon black (10 phr) were used as conventional fillers in these composites. The mechanical and curing properties of the developed NR-based hybrid composites were evaluated and compared with control samples. It was noted that the maximum tensile strength, tear strength, hardness, and Young's modulus were increased by 8%, 9.39%, 6.35%, and 18.31% in NR/EPDM/GTR (95/5/10), while for NR/CR/GTR (95/5/10), 17.1%, 10.71%, 6%, and 31.72% over the control sample. The elongation at break was reduced by 29.11% in NR/EPDM/GTR (95/5/10), but for NR/CR/GTR (95/5/10) was 21.65% over the control sample. The cure properties like scorch time (tS2 ) and cure time (tC90 ) were decreased, while minimum torque (ML ) and maximum torque (MH ) were enhanced with the incorporation of GTR 10 phr in both the composites when compared with the control sample. The addition of GTR increased the sulfur in the cured composites, which was confirmed in EDS analysis. Based on the microstructure and thermogravimetric analysis, GTR particles were uniformly distributed, and the thermal stability was increased by 19.6% and 21.5% in NR/EPDM/GTR (95/5/10) and NR/CR/GTR (95/5/10) composites, respectively, over the control sample. The absorption peaks of NR, EPDM, CR, and GTR elements in the developed composite were identified using Fourier Transform Infrared spectroscopy (FTIR). In the NR/EPDM composite, the glass transition temperature (Tg ) was increased from −60.7°C to −58.17°C, but for the NR/CR composite, it was −61.43°C to −58.96°C. Finally, the inclusion of 10 phr of GTR was recommended to be suitable for NR with EPDM or CR composites.